STRATEGI INDONESIA DALAM MENINGKATKAN KUNJUNGAN WISATAWAN KOREA SELATAN KE INDONESIA TAHUN 2015-2017 - Nadea Ariessya; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to explain how the strategy undertaken by Indonesia in an effort to increase the number of foreign tourists from South Korea. Indonesia, which has long good bilateral relations with South Korea in various fields has been a bridge to continue to improve relations between the two countries. Counting the number of unstable South Korean tourists visiting Indonesia made the Indonesian government move quickly to set the strategy to be used to attract South Korean tourists.This research method is obtained from books, journals, and websites that support the hypothesis. In this paper, the author uses the perspective of Neorealism with the theory of Foreign Politics and the concept of tourism. The author uses the level of analysis of the nation state as an actor in international relations. This study uses qualitative research methods.The result of this study is that the Indonesian government uses an international-scale promotion with BAS (Branding, Advertising, and Selling) strategy approachers, marketing aspects using the DOT (Destination, Origin, and Time) approach, and media aspects using the POSE (Paid Media, Owned Media) approach. , Social Media, And Endorser) to increase tourists visiting South Korea. From 2015 to 2017 the international promotion carried out by the Indonesian government to attract tourists from South Korea is through Visit Indonesia, arts and cultural festivals, and also through South Korean reality show television programs that show the beauty of Indonesian tourism.Keywords: Strategy, BAS Strategy, Indonesia Tourism, South Korean Tourist, International Promotion.